KARAKTERISTIK SOSIOLOGI HUKUM - Muhammad Sibawaih (JURNAL CERDAS HUKUM, 2023)
Basically, regulations are made aimed at creating justice, order, protection of human rights and benefits. Therefore, it is not an exaggeration if one argues that the existence of law is the supreme commander in a state order. It means that all matters related to the activities, conduct and actions carried out by the public and policy activities and decisions made by the ruling elites or the government must be within the corridors of the legal regulatory apparatus or laws applicable within the State. Indonesia, for example, is one of the countries that label its country as a country based on law. This can be seen in the Basic Law of 1945 the third amendment in article 1 paragraph (3) there is stated that "Indonesia is a country of law. The legal system used in Indonesia until now is sourced from three components of the legal system. namely the western legal system, Islamic law and customary law. These three legal systems are important components in every legal formulation and manufacturing agenda in Indonesia. The focus of this article is on trying to capture the scope and characteristics of the law